2019
DOI: 10.12688/wellcomeopenres.15565.1
|View full text |Cite
|
Sign up to set email alerts
|

High dose oral rifampicin to improve survival from adult tuberculous meningitis: A randomised placebo-controlled double-blinded phase III trial (the HARVEST study)

Abstract: Background: Tuberculous meningitis (TBM), the most severe form of tuberculosis (TB), results in death or neurological disability in >50%, despite World Health Organisation recommended therapy. Current TBM regimen dosages are based on data from pulmonary TB alone. Evidence from recent phase II pharmacokinetic studies suggests that high dose rifampicin (R) administered intravenously or orally enhances central nervous system penetration and may reduce TBM associated mortality. We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Despite the advent of anti-TB chemotherapy and corticosteroids most deaths (95%) from TBM will still occur by 6 months [69]. An observational report in 1961 on long-term outcomes in children with TBM, was the first to highlight persistent neurodevelopmental sequelae years following completion of TB treatment [90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the advent of anti-TB chemotherapy and corticosteroids most deaths (95%) from TBM will still occur by 6 months [69]. An observational report in 1961 on long-term outcomes in children with TBM, was the first to highlight persistent neurodevelopmental sequelae years following completion of TB treatment [90].…”
Section: Discussionmentioning
confidence: 99%
“…A recent model-based meta-analysis using emerging data from adult trials showed a strong positive correlation between rifampicin concentrations and survival, with doses of at least 30 mg/kg predicted to improve survival substantially compared to 10 mg/kg [68]. A dose of 35 mg/kg daily is being tested in a definitive Phase 3 trial [69] but higher mg/kg doses than that will be needed to achieve adult-equivalent exposures in children [70]. In children, a small trial suggested that a dose increase to 30 mg/kg improved neurocognitive function compared to standard dosing [71].…”
Section: Treatmentmentioning
confidence: 99%
“…Some of these patients’ regimen were supplemented with another drug such as levofloxacin or moxifloxacin. Some research showed that high dose of RIF (20–35 mg/kg administered orally, and standard dose of INH) was able to improve treatment outcomes due to a higher RIF concentration in plasma and CSF, especially when RIF was administered intravenously [ 20 , 21 ]. Other research did not reach the same conclusion above, though [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively reviewed data from patients who presented with symptoms of a central nervous system (CNS) infection to Kiruddu National Referral Hospital and Mbarara Regional Referral Hospital, Uganda, between April 2017 and March 2022. Patients underwent lumbar puncture as part of the screening process for three clinical trials ( 34 36 ) and an observational cohort focused on meningitis diagnostics ( 9 ). Following informed consent, a diagnostic lumbar puncture was performed with CSF collection.…”
Section: Methodsmentioning
confidence: 99%